PERAN KEPOLISIAN SEKTOR KECAMATAN SAJAD DALAM PENANGANAN COVID-19 TAHUN 2020 - Kurnia; Rifqi Muhammad; Lamazi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
The purpose of this study was to determine the role of the Sajad district Police Sector in handling Covid-19. Covid-19 is an infectious disease causedby a new type of virus and is a problem that must be paid special attention to, the impact caused by Covid-19 appears in various aspects of life, causing human activities to be constrained. The role played by the Sector Police is a da’wah activity, namely to call for goodness with the aim of breaking the chain of the spread of Covid-19. This study uses a descriptive approach with qualitative approach types. The research results show that theinvolvement of the sector police in handling Covid-19 is a companion to the task force team to accelerate the handling of Covid-19. The sector police discipline the public to comply with government regulations such as health protocol and avoid associations. The involvement of community leaders in handling covid-19 is participating and collaborating. Supporting and inibitng factors are village officials supporting the implementation o handling Covid-19. Meanwhile, the obstacle is the geographical location thet is difficul to reach during the implementation such as patrols and routine disinfectant spraying activities.